Puisi Nikah Sungai dan Nikah Pisau karya Dorothea Rosa Herliany dalam perspektif ekofeminis Mary Daly - Iswadi Bahardur; Putri Dian Afrinda; Rina Sartika (Universitas Mulawarman, 2023)
This research is motivated by the problem of the relationship between women and nature with male power which is reflected poetically by Dorothea Rosa Herliany in two poems entitled